The Essence of Community Values in the Era 5.0 Perspective of Islamic Education Philosophy - Syafaruddin, Baso (ETDC: Indonesian Journal of Research and Educational Review, 2023)
This article explores the fundamentals of social values in the 5.0 era from the viewpoint of Islamic educational philosophy, which highlights the need to take action to stop the period's social values from deteriorating. The study's findings demonstrate that the idea of society's Islamic education philosophy holds that it ontologically promotes the growth of moral principles in social behavior. Islamic educational philosophy serves as a platform for defending a society built on the capacity for original thought, tolerance for diversity, and the promotion of social harmony. The difficulties of Islamic educational philosophy in the process of forming society are evident in circumstances that demand the emergence of unique characteristics, necessitating a reconstruction of Islamic educational philosophy study and the demands of societal development in the context of the 5.0 era.